Performance Of Coriander Cultivars For Green Leaf Production Under Late Sowing Condition - Chaulagain, R; Pant, SS; Thapa, RB; Sharma, MD (Journal of Agriculture and Environment, 2013)
A field experiment was conducted at the research farm of Institute of Agriculture and Animal Science, , Chitwan, Nepal from December 2009 to March 2010 to study the green leaf production potential of coriander (Coriandrum sativum L.) cultivars. Ten cultivars of coriander were evaluated in a Randomized Complete Block Design (RCBD) replicated three times. Coriander Local, Marpha Local, Mallika, Surabhi and Kalmi Chhattedar showed better performance as compared to others on growth, yield and quality parameters. The highest green leaf yield (10.09 mt/ha) was recorded in Coriander Local followed by Mallika (9.54 mt/ha), Surabhi (9.40 mt/ha) and Kalmi Chhattedar (9.24 mt/ha). Surabhi was found promising cultivar under late sowing condition because if its highest rosette diameter, number of basal leaves and length of basal leaf Hence, there is good scope of coriander cultivation for green leaf production, however, it is more suitable to sow the seeds in usual tome of sowing for the better performance of all the cultivars. The Journal of Agriculture and Environment Vol:12, Jun.2011, Page 67-73 DOI: http://dx.doi.org/10.3126/aej.v12i0.7565